Fast determination of four active compounds in Sanqi Panax Notoginseng Injection samples by high‐performance liquid chromatography with a chemometric method. Issue 9 (18th March 2015) - Li, Bao Qiong; Chen, Jing; Wu, Tong Xing; Zhai, Hong Lin; Zhang, Xiao Yun
<x xml:space="preserve">Abstract</x> The application of chemometric methods could decrease the requirements of separation and simplify time‐consuming pretreatment and experimental optimization. In this report, the accumulated projection method was developed and utilized for the rapid simultaneous quantification of four active components (notoginsenoside R1, ginsenosides Rg1, ginsenosides Re, and ginsenosides Rb1) in Sanqi Panax Notoginseng Injection samples. The proposed method is based on the three‐dimensional fingerprint spectra obtained from high‐performance liquid chromatography coupled with photodiode array detection. Although the chromatograms consisted of overlapping peaks, retention time shifts, and unknown interference, all established models showed good linearity (R > 0.9869) within test ranges. The relative standard deviation for intra‐ and interday precision of the four compounds did not exceed 2.4 and 4.7%, respectively, and the overall recovery was 91.2–106.8%. Compared with N‐way principal component analysis, our method provides more satisfactory results, which indicate that the proposed approach is simple, fast, and reliable for the determination of the four analytes in Sanqi Panax Notoginseng Injection samples.